SOSIALISASI PENGUATAN STANDAR PENJAMINAN MUTU INTERNAL BERBASIS 5 ASAS PERJUANGAN BUNG KARNO (Refleksi dan Penelusuran Identitas Kampus Nasionalis) - Johan Erwin Isharyanto; Adhi Putra Satria (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
This article is the result of dedication and socialization activities aimed at examining and analyzing the principles of Bung Karno's struggle, as well as their relevance to the implementation of higher education in Indonesia. This article emphasizes the exploration of views, ideas, and concepts based on data, both secondary and primary data, which are then presented descriptively qualitatively. The results of the analysis and literature review show that towards the principles of Bung Karno's struggle in his ideas include 5 main principles, namely, among others, the radical-revolutionary principle, machtvorming, mass-action, non-cooperation, self-help & self-reliance. These principles have relevance to the implementation of higher education especially in campuses characterized by nationalism, where these principles can be used as guidelines in determining the content of how internal quality assurance standards are made, implemented, and consistently implemented to achieve graduates who truly have character and true nationalist spirit.